Does Capital Asset Pricing hold in Pakistan Stock Exchange? An Application of Seemingly Unrelated Regression - KHAN, AINY; BALOCH, SHAHNAWAZ; ARIF, KASHIF; ALVI, JAHANZAIB (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is to critically evaluate role of Capital Asset Pricing Model with the respect to Pakistan Stock Exchange through applying Seemingly Unrelated Technique of Regression (SUR) model. The core crux of this research was to investigate new extrinsic opportunity of growth for the firms listed in Pakistan Stock Exchange by optimizing risk. The data set includes Jan-2014 to Dec-2016 comprising all industrial sectors listed at PSX and concluded on behalf of its volume. KSE-100 Index was kept as proxy for synthetic market portfolio. Composed portfolios are solely on non-financial firms of PSX. Trade volume was kept as benchmark for composition and split up them into ten set of portfolio depending on higher to lower side of trade volumes in descending order with assigning weightage to 10% each. Result witnessed that effect of market returns is solely base on trade volume. The results was assessed by using regression and Seemingly Unrelated Technique of Regression (SUR), moreover results also showcased, beta is quite significant except a single model, and the same with alpha exhibiting the value around zero, in the light of results, it has been concluded that CAPM holds in the context of PSX.